2011
DOI: 10.1016/j.rbmo.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone-based prediction model for a live birth in assisted reproduction

Abstract: Prediction of assisted reproduction treatment outcome has been the focus of clinical research for many years, with a variety of prognostic models describing the probability of an ongoing pregnancy or a live birth. This study assessed whether serum anti-Müllerian hormone (AMH) concentrations may be incorporated into a model to enhance the prediction of a live birth in women undergoing their first IVF cycle, by analysing a database containing clinical and laboratory information on IVF cycles carried out between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 45 publications
5
82
1
6
Order By: Relevance
“…The two markers are strongly related to the quantitative aspect of ovarian reserve; hence a low AMH and/or AFC are highly indicative of possible low number of growing follicles and oocyte following ovarian stimulation. Moreover, both low AMH and AFC have been associated to reduced pregnancy and live birth following IVF independent of age [35][36][37][38][39][40][41]. This may indicate some relationship between quantity and quality of oocytes, with a The present study because of its retrospective design has relevant limitations, including a biased selection of women recruited for the study.…”
Section: Discussionmentioning
confidence: 86%
“…The two markers are strongly related to the quantitative aspect of ovarian reserve; hence a low AMH and/or AFC are highly indicative of possible low number of growing follicles and oocyte following ovarian stimulation. Moreover, both low AMH and AFC have been associated to reduced pregnancy and live birth following IVF independent of age [35][36][37][38][39][40][41]. This may indicate some relationship between quantity and quality of oocytes, with a The present study because of its retrospective design has relevant limitations, including a biased selection of women recruited for the study.…”
Section: Discussionmentioning
confidence: 86%
“…The introduction of AMH in reproductive endocrinology can be considered a revolution in the prediction of the ovarian reserve and response , resulting in the individualization of treatment strategies and counseling of couples regarding the likelihood of the success of IVF treatment [10,11]. There is a trend toward using AMH to individualize treatment strategies and optimize the overall efficacy of IVF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the rate of decline in mean AMH values was 0.2 ng/ml/year through age 40, with AMH values diminishing to 0.1 ng/ml/year thereafter. In a longitudinal observational study, de Vet et al [11] investigated whether serum concentrations of AMH had the potential to be used as a marker for ovarian aging. In the interval between two visits, which ranged from 1.1 to 7.3 years (mean, 2.6 ± 1.7 years), the concentrations of AMH decreased significantly over time (median value, 2.1 g/l at visit 1 vs. 1.3 g/l at visit 2), whereas the number of antral follicles and levels of FSH and inhibin B did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in more selected IVF populations reported that the greater the proportion of women with diminished ovarian response, the greater the utility of screening them with serum AMH [11,14,25,26]. Because maternal age remains the strongest prognostic factor in IVF, the models based on age and serum AMH appear to be more informative than each marker alone [15,19]. The cutoffs identified in this study for serum AMH should not be extrapolated to other settings.…”
Section: Discussionmentioning
confidence: 76%
“…However, the practical utility of this marker to predict pregnancy is currently uncertain, and probably limited by the lack of association of AMH with embryo quality [12]. Only recently, studies have evaluated the ability of day 3 AMH to predict the likelihood of a live birth, and the balanced conclusion would be that the women at the extremes of basal AMH have different live birth rates (8); however, no single AMH cutoff has achieved a satisfactory combination of sensitivity, specificity, and predictive power for this outcome [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%